The intimacy-power relationships in the usage of direct criticism in Chinese: a reflection of rapport management - Xin Weng; Qiaoyun Liao (Language and Cognition)
This study explored the intimacy-power patterns in Chinese direct criticism and how this may reflect native Chinese speakers’ consideration of rapport management. With data retrieved from BCC, a representative corpus of modern Chinese, the analyses identified the intimacy degree and power relativity of the interlocutors where direct criticism was used. Results revealed that native Chinese speakers use direct criticism mostly in close and equal relationships followed by distant and equal ones; also, direct criticism with different criticizing markers manifests their uniqueness that close and equal relationships appeared more in criticism with “你太(nitai) + adj.”, “我看你(wokanni)” and “你真是(nizhenshi)” while distant and equal relationships appeared more frequently in criticism with “你这(nizhe) + n. /adj.”. These results reflect that native Chinese speakers adopt rapport-maintaining/rapport-enhancing orientations by using criticism more often in close and equal relationships, together with their tendency to ignore rapport, especially in distant and equal relationships. To conclude, this study reveals the patterns of intimacy-power relationships in Chinese speakers’ usage of direct criticism, which reflects their awareness of rapport management. Overall, it provides insights into our understanding of the nature of the speech act of criticism.